2016
DOI: 10.1021/acs.macromol.6b01216
|View full text |Cite
|
Sign up to set email alerts
|

Pendant Homopolymer and Copolymers as Solution-Processable Thermally Activated Delayed Fluorescence Materials for Organic Light-Emitting Diodes

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(101 citation statements)
references
References 41 publications
2
96
0
Order By: Relevance
“…Thesecond one is directly using asmall molecular TADF unit, which is introduced into the main chain or side chain of ap olymeric host. [22][23][24][25] Unfortunately, the intrinsic low triplet energy,e specially for conjugated polymers,o ften leads to the loss of triplet excitons and thus poor device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Thesecond one is directly using asmall molecular TADF unit, which is introduced into the main chain or side chain of ap olymeric host. [22][23][24][25] Unfortunately, the intrinsic low triplet energy,e specially for conjugated polymers,o ften leads to the loss of triplet excitons and thus poor device performance.…”
Section: Introductionmentioning
confidence: 99%
“…The best performing non-conjugated TADF polymer in this review is TADF-P2 with a device that gave an EQE of 20.1%, 21 yet it should be noted that the polymer was doped in a large amount (90 wt.%) of small-molecule mCP host as the emitting layer. On the other hand, neat TADF-P1 as the emitting layer gave a decent EQE of 10%.…”
Section: Thermally Activated Delayed Fluorescence (Tadf) Polymersmentioning
confidence: 99%
“…78 A follow-up study by the same group investigated the impact of styrene content in a series of copolymers of styrene and PTZ-DBTO2 chromophore on their photophysical properties and device performance. 21 A homopolymer of PTZ-DBTO2 was also synthesized and studied. It was found that, with increasing styrene composition in the polymers, the contribution of the delayed fluorescence became more significant due to suppressed triplet-triplet annihilation (TTA) because the concentration of PTZ-DBTO2 chromophore in the polymer was diluted.…”
Section: Thermally Activated Delayed Fluorescence (Tadf) Polymersmentioning
confidence: 99%
See 2 more Smart Citations